Analysis Of Health Service Policy In The Context Of Accelerating The Reduction Of Infant Mortality Rates In Seruyan Regency In 2023 - Chairil Huda; Risky Kusuma Hartono (Jurnal EduHealth, 2024)
In achieving a reduction in the Infant Mortality Rate, Regional Governments have a very important role in policy programs in the health sector, especially maternal and child health. The SPM achievements related to the Infant Mortality Rate in Seruyan Regency have not yet reached the SPM target in accordance with Minister of Health Regulation number 4 of 2019 concerning minimum service standards in the health sector. This research aims to analyze health service programs in an effort to accelerate the reduction of infant mortality rates in Seruyan Regency in 2023. The research method is qualitative, involving 7 groups of informants selected based on the capacity and knowledge of the resource persons related to health services in reducing infant mortality rates in Seruyan Regency. . Data analysis used in data processing uses the Milles and Huberman method and Fishbone Diagram (fishbone analysis). Data validation in this research uses source triangulation and method triangulation. The results of the research found that health services in order to accelerate the reduction of infant mortality rates in Seruyan Regency in 2023 have not been effective, it is known that the implementation of regulations related to maternal and child health services has not been optimal, has not been efficient, there is no budget allocation for the newborn health service program in 2022, has not been responsive because the integrated K6 antenatal care (ANC) service at the Community Health Center is not yet optimal, the competence and distribution of health workers, the maternal neonatal emergency referral service is not yet optimal, there are still early pregnancies, and the socio-cultural culture of indigenous peoples who still give birth at home and are assisted by village shamans.